PERCERAIAN USIA TIGA TAHUN PERKAWINAN DARI PASANGAN MUDA - Jundan, Gozwan (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2020)
Law No. 1 of 1974 concerning marriage explains that marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy family (household) based on the divinity of the Almighty. However, it was found several decisions of the Garut Religious Court which showed the age of marriage which lasted a short period of time. This study aims to determine the factors causing divorce at the age of 3 years of marriage from a young couple in the Garut Religious Court, to find out the legal reasons for judges for divorce at the age of 3 years of marriage from a young couple in the Religious Court of Garut and the judge's view of the granting of a 3 year marriage divorce decision. from a young couple in the Garut Religious Court. The results showed that the factors causing divorce at the age of 3 years of marriage can be classified into 3 main causes, namely: disputes and quarrels, lack of responsibility from the spouse and interference from outside parties. The legal reasons for judges who are sufficient to meet the reasons for divorce based on the law of several examples of decisions include: based on the information submitted before the trial the judge found the fact that between couples often quarrels and disputes occur and are not responsible for obligations in fulfilling the needs of living , as well as the parties split up residence.